Which soft lens power is better for piggyback in keratoconus? Part II - Romero-Jimenez, Miguel (2015)
Purpose: To evaluate how soft lens power affects rigid gas-permeable (RGP) lens power and visual acuity (VA) in piggyback fittings for keratoconus. Methods: Sixteen keratoconus subjects (30 eyes) were included in the study. Piggyback contact lens fittings combining Senofilcon-A soft lenses of −6.00, −3.00, +3.00 and +6.00 D with Rose K2 RGP contact lenses were performed. Corneal topography was taken on the naked eye and over each soft contact lens before fitting RGP lenses. Mean central keratometry, over-refraction, RGP back optic zone radius (BOZR) and estimated final power as well as VA were recorded and analyzed. Results: In comparison to the naked eye, the mean central keratometry flattened with both negative lens powers (p < 0.05 in all cases), did not change with the +3.00 soft lens power (p = 1.0); and steepened with the +6.00 soft lens power (p = 0.02). Rigid gas-permeable over-refraction did not change significantly between different soft lens powers (all p > 0.05). RGP’s BOZR decreased significantly with both positive in comparison with both negative soft lens powers (all p < 0.001), but no significant differences were found among negative- or positive-powers separately (both p > 0.05). Estimated RGP’s final power increased significantly with positive in comparison with negative lens powers (all p < 0.001), but no significant differences were found among negative or positive lens powers separately (both p > 0.05). Visual acuity did not change significantly between the different soft lens powers assessed (all p > 0.05). Conclusion: The use of negative-powered soft lenses in piggyback fitting reduces RGP lens power without impacting VA in keratoconus subjects.